(untitled) (Heritage, 2025)
This work will deal with the role of Serbian diplomacy in the construction of the first railway on Serbian territory. The Duchy was granted independence at the Berlin conference in 1978, something that brough along with it the obligation to construct a railroad through its territory to connect Europe with Constantinople. Serbian diplomats worked to achieve that goal in the years that led up to the railway’s completion: They included one of the policy’s chief standard-bearers, the Serbian sovereign, Milan Obrenović, as well as government representatives Jovan Ristić and Milan Piroćanac, and Minister and Ambassadors Čedomilj Mijatović and Stojan Novaković, among other actors. Numerous tribulations, such as accusations of corruption on the part of members of the government and parliament, and the bankruptcy of the ‘General Union’ led to internal political crises that had to be addressed almost exclusively at the highest levels of internal politics as well as during the course of negotiations with European powers. Credit for the successful construction of the railways ultimately goes to the above-mentioned figures.